Recycling Ophthalmic Lens Wastewater in a Circular Economy Context: A Case Study with Microalgae Integration - FAUSTO, RUI (MDPI, 2024)
Water pollution poses a global threat to ecosystems and human health and is driven by the presence of various contaminants in wastewater, including nano- and microplastics. Despite the magnitude of this problem, the majority of global wastewater is released untreated into water bodies. To combat this issue, a multi-strategy approach is needed. This study explores a circular economy-based solution for treating emerging pollutants, particularly wastewater from ophthalmic spectacle lens production. Our approach integrates solid waste materials into polymeric and cement matrices while also utilising wastewater for microalgae cultivation. This innovative strategy focuses on biomass generation and economic valorisation. By adopting a circular economy model, we aim to transform environmental pollutants from wastewater into valuable organic products. A key component of our approach is the utilisation of microalgae, specifically Nannochloropsis sp., known for its high lipid content and resilience. This microalgae species serves as a promising biobased feedstock, supporting the production of innovative biobased products, such as biopolymers, for ophthalmic lens manufacturing. Our interdisciplinary approach combines microalgae technology, analytical chemistry, cement production, and polymer processing to develop a sustainable circular economy model that not only addresses environmental concerns, but also offers economic benefits. This study underscores the potential of harnessing high-value products from waste streams and underscores the importance of circular economy principles in tackling pollution and resource challenges.
Keywords: Biobased Products; Biopolymers; Bioremediation; Circular Economy; Microalgae; Ophthalmic Lenses; Recycling; Sustainability